Penilaian Aspek Fungsional Instalasi Rawat Inap VIP Flamboyan RSUD Sayang Cianjur - Pramono, Syaref; Setyowati, Erni; Hardiman, Gagoek (Jurnal Arsitektur dan Perencanaan (JUARA), 2020)
RSUD Sayang as the only Class B hospital that has become a reference in Cianjur Regency with the problem of lack of rooms in IRNA VIP Flamboyan. The purpose of the study was to obtain the results of the Flamboyant IRNA Post-Occupancy Evaluation (POE) analysis. Emphasis is placed on functional aspects because the age of the building is10 years old so that it is suspected that the building function does not meet IRNA VIP requirements which results in a low level of user satisfaction. The research method is qualitative with descriptive analysis to objectively analyze the existing condition of the building. The analysis shows that the condition of the VIP class building has not met the standard of inpatient rooms and the functional aspects of the building have not been met so that residents feel uncomfortable